"Xilala is only treated with a good hand": a study on the treatment of malnutrition in Mozambique - Janete Ismael Mabuie Gove; Rubia Carla Formighieri Giordani; Vitor Henrique de Siqueira Jasper; Arune Estavela; Islândia Bezerra (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2021)
Abstract: In Mozambique old and new evils of body and spirit intertwine, thus allowing particular contours to modern life. Traditional diseases are reconfigured along the lines of a new thinking, and what Western medicine calls malnutrition is defined as xilala by the local traditional thinking. This study aimed to understand the point of view of both caregivers (mothers and grandmothers) of children participating in a Nutritional Rehabilitation Program and ethnomedicine experts, who find themselves entangled in a complex set of relationships through which different forms to comprehend body, health, and disease circulate. The supplement, as an object, has a life of its own and takes on new meanings when it leaves the hospital. When its use happens at home, it acquires a particularity: it becomes food. Thus, it ceases to be something inert and impersonal, which is a feature of standard medicine of the health institution. The local view centered on ethnomedicine is based on the certainty that a situation affecting a child cannot have a healing outcome if not by traditional medicine. Biomedical rationality erected from the confluence of the biological and technical sciences with their scientific postulates does not constitute the authorized discourse in this context.